Psammon rotifers in Central Vietnam, with the descriptions of three new species (Rotifera: Monogononta) - Dang, Mau Trinh; Segers, Hendrik; Sanoamuang, La-Orsri (Zootaxa, 2015)
In order to address the dearth of information on Rotifera in Vietnam, and especially on rotifers inhabiting freshwater psammon in Southeast Asia, we collected and examined twenty-five hygropsammon samples from Bau Thiem Lake, Thua Thien Hue Province, central Vietnam. A total of eighty-nine species-level rotifer taxa were identified, belonging to 21 genera and 13 families. Of these, 48 taxa (54%) are new to Vietnam, including three species, Lecane climacois Harring & Myers, 1926, Notommata cerberus (Gosse, 1886) and Trichocerca intermedia (Stenroos, 1898) that are new to the Oriental region, and three species, Lecane phapi n. sp., Lecane dorysimilis n. sp. and Trichocerca bauthiemensis n. sp. that are new to science. These, and some additional rare species are commented upon and illustrated. We estimated that the α-diversity of psammon rotifers in Bau Thiem Lake may be as high as 99 (SD=8.4; Chao2) or 115 (Jacknife2) taxa. These results indicate a high potential of rotifer diversity in the hygropsammon at Bau Thiem Lake, central Vietnam.